Effect of stainless steel oxygen dissolver in the piling fermentation of sauce-flavor baijiu - Zhao, Hubing; Huo, Yingyu; Yang, Gangren; Liu, Xiaozhu; Li, Zhongtai; Luo, Diao; Zhao, Xiaoyu; Li, Xu (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
In order to solve the abnormal fermentation problems caused by the slow and difficult temperature rise in the saccharification piling during the fermentation of sauce-flavor baijiu under low temperatures in winter. A special oxygen dissolving device made of stainless steel was applied in the second sorghum input of sauce-flavor baijiu, as well as the 1th and 2th rounds of saccharification piling fermentation in this study. In addition, its effects on the saccharification piling temperature, the 1th and 2th rounds of physical and chemical indicators, microbial population, and flavor components are analyzed. The results indicate that the use of a stainless steel oxygen dissolver significantly increased the “piling core” temperature of a saccharification piling and that this improvement was highly correlated with the oxygen dissolver. Additionally, it decreased the water content, sugar concentration, and acidity of the “piling core” of the saccharification piling, all of which were negatively correlated with the height of the dissolved oxygen reactor. Furthermore, the stainless steel special dissolved oxygen device also facilitated the growth and reproduction of saccharification piling microorganisms, particularly yeast. The use of the stainless steel special dissolved oxygen device, therefore, resulted in an increase in the concentration of acetaldehyde, ethyl acetate, propanol, isoamyl alcohol, β-phenylethanol, ethyl palmitate, and other flavoring compounds. Accordingly, the stainless steel special oxygen dissolving device demonstrates a significant application potential in the 1th and 2th rounds of saccharification piling fermentation of sauce-flavor baijiu.